Answer:
29. See table below
30. See attached graph
31. The slope is m= 0.10
The slope represent the cost for every additional call minute.
Step-by-step explanation:
The cost is $0.5 first minute and $0.10 for any additional minutes
If c is the total cost of a call that last t minutes then;
c= 0.10t + 0.5-----where t is the time the call lasted
29. Use the equation above to create the table as;
t {x} c{y}
1 0.6
2 0.7
3 0.8
4 0.9
5 1.0
6 1.1
The graph of this plot is as attached , where the coordinates are
{1,0.6} , {2,0.7} ,{3,0.8} ,{4,0.9} ,{5,1.0}, {6,1.1}
The slope can be found using the formula;
m=Δy/Δx
m= 1.1 - 0.6 / 6-1
m= 0.5 / 5 = 0.10
The slope represent the cost for every additional call minute.
Answer:
Let's begin by writing the mathematical equations given by the sentences.
Let X = smaller number
Let Y = larger number
The first sentence tells us
X + Y = 38
The second sentence tells us
X = Y/3 + 6
Since you weren't given a specific method to use, you can use either the substitution method or the elimination(addition) method, whichever works best for you.
Since the 2nd equation has the X isolated, I'm going to isolate the X in the first equation,
X = 38 - Y
Since both equations are equal to X, I can set them equal to one another and solve for Y.
Y/3 + 6 = 38 - Y
Y + 18 = 114 - 3Y
4Y = 96
Y = 24
Then use either of the two original equations to solve for X
X + Y = 38
X + 24 = 38
X = 14
Step-by-step explanation:
PLS MAKE ME AS BRAINLIST
There are so many types of angles, let's see what we've got here!
--(5x - 17) and 48 are alternate interior angles, which means that they are congruent.
--(5x - 17) and y are supplementary angles.
--48 and y are same-side interior angles, which means that they are also supplementary.
Let's solve for x first.
5x - 17 = 48
5x = 65
x = 13
Now, let's solve for y.
48 + y = 180
y = 132
Hope this helps!! :)
Answer:
63 calories
Step-by-step explanation:
Divide the number of calories by the number of servings
calories/servings
252/4
63
So, there are 63 calories per serving
Hope this helps!
f ( - 2 ) = 5 × 3^( - 2 )
f ( - 2 ) = 5 × 1/9
f ( - 2 ) = 5/9